(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
More than 45 hydroelectric power stations are used to meet the national economy of the republic, including agriculture, and their age is 30-40 years or more. Currently, the total installed power of power plants belonging to "Uzbekenergo" JSC is 14140 MW. Of them, 12,129 MW are due to thermal power plants and 1,878.7 MW are to hydropower plants. Natural gas, fuel oil, and coal are used as fuel in thermal power stations. All the energy resources of Uzbekistan have developed operational resources, and their further use can lead to a decrease in the stability and efficiency of power plants.